Neuropsychological and behavioral implications in childhood and adolescence from the use of screens (Research, Society and Development, 2020)
The use of screens by children and adolescents has become increasingly common and accessible. The fact aroused the attention of the scientific community and the concern of parents, teachers and professionals regarding the possible neuropsychological and behavioral effects. This article aims to present and discuss the possible neuropsychological implications of the use of screens in childhood and adolescence, using the narrative bibliographic review method. The study showed that the use of screens in the family context occurs increasingly and impacts socialization, interaction and daily interaction between parents and children, significantly reducing them. In addition, the developing brain is impacted by any and all experiences, including the use of screens. The studies found demonstrate impacts on neuropsychological functions such as: attention, memory, language, executive functions, and impairments in social, emotional and behavioral aspects. As well as, the excessive use of electronics from screens can lead to dependence on them. Further studies are needed to clarify the real impact on the structuring of the brain in formation. In terms of neuropsychological functions, studies are needed to clarify the long-term effects.